CASE REPORT ON BULLOUS PEMPHIGOID: A FATAL SKIN CONDITION - Kela*, Punam; Nanday , Atharva; Desai , Ujwala (Innovative Journal of Medical and Health Sciences, 2020)
Bullous pemphigoid (BP) is a fatal skin condition which is manifested as diffuse eczematous, pruritic lesions which is afterwards; appear as tense blistering lesions filled with clear fluid which is commonly observed in elderly. Direct immunofluorescence is used as the definitive standard for the diagnosis of BP. Line of treatment for BP includes drugs which are anti-inflammatory such as topical steroids and sulfonamides; second line of treatment includes the immune-suppressant agents such as azathioprine, systemic steroids and last line of therapy includes the agent which increases the elimination of abnormal antibodies from plasma. These may include the treatment options such as plasmapheresis and intravenous immunoglobulin. Key Words Bullous Pemphigoid, Autoimmune disease, Skin conditions